Augmented reality of food plants as a biodiversity learning media for 10th grade high school: A feasibility analysis - Ayu Putri Herwidiah; Syamswisna Syamswisna; Asriah Nurdini Mardiyyaningsih (Department of Biology Education, Universitas Pendidikan Indonesia, 2023)
Submission of material that only uses printed books, printed pictures, and power points as well as limited infrastructure hinders student learning experiences. Augmented reality (AR) interactive media is one of the innovations to make it easier to guide material to make it more interesting and interactive. So this study aims to describe the feasibility of interactive multimedia augmented reality of food plants as a support for learning biodiversity in 10th grade of senior high school. The augmented reality system was created using Vuforia and Unity 3D software, and involved curriculum analysis, storyboard design, data collection, marker creation, and 2D object design of food plants, followed by AR media creation. This research used a quantitative descriptive method, data collection is carried out using validation instruments of material experts and media experts. Validators consist of 3 material experts and 3 media experts. The validation obtained an average total validation (RTVtk) of material experts at 3.83 and media experts at 3.80. This assessment is considered valid because it meets the validity standard, namely 3â‰¤mRTVtkâ‰¤4. Thus, interactive multimedia augmented reality is suitable to be used as a learning medium in the sub-material of utilizing biodiversity as food plants in 10th grade of high school.